Blockchain Technology Innovation for Transparency and Reliability in Accounting Practices in Egypt - Abd Al Aziz (PT. BATARI EDU CALYA, 2024)
This study investigates the adoption and implementation of blockchain technology innovation to enhance transparency and reliability in accounting practices within the Egyptian context. As digital transformation continues to reshape financial reporting and auditing processes globally, understanding the factors influencing blockchain adoption in emerging economies is increasingly critical. Employing a quantitative research methodology with structural equation modeling (SEM) using SmartPLS software, this research examines the relationships between perceived usefulness, system quality, information quality, and the actual use of blockchain-based accounting information systems among Egyptian accounting professionals. The findings reveal that quality dimensions significantly influence blockchain adoption intentions, while organisational support and professional development mediate to enhance implementation success. This research contributes to the growing body of literature on technology adoption in accounting by providing empirical evidence from an emerging market perspective, offering practical implications for policymakers, accounting firms, and regulatory bodies seeking to modernize Egypt's financial infrastructure through blockchain integration.